Discrimination training of phonemic contrasts enhances phonological processing in mainstream school children - Moore, DR; Rosenberg, J; Coleman, J (2005)
Auditory perceptual learning has been proposed as effective for remediating impaired language and for enhancing normal language development. We examined the effect of phonemic contrast discrimination training on the discrimination of whole words and on phonological awareness in 8- to 10-year-old mainstream school children. Eleven phonemic contrast continua were synthesised using linear interpolation coding from real speaker endpoints. Thirty children were pre-tested on the Word Discrimination Test (WDT) and the Phonological Assessment Battery (PhAB). Eighteen then trained for 12 × 30 min sessions over 4 weeks using an adaptive three interval two alternative phonemic matching task. The remaining children participated in regular classroom activities. In Post-testing, trained children significantly increased their age-equivalent scores on both the WDT and PhAB by about 2 years. For the PhAB, no improvement was found in the controls. Enhanced performance in the trained children was maintained in a delayed test 5-6 weeks following training. Enhancements on the trained discriminations were weak and variable. The results indicate a dramatic improvement in phonological awareness following phonemic discrimination training without matching perceptual learning. © 2004 Elsevier Inc. All rights reserved.